Studi Perencanaan Pipa Jaringan Distribusi Air Bersih Pdam di Desa Klagen dan Ngadiboyo Kecamatan Rejoso Kabupaten Nganjuk - Naufal Yudhistira; Eko Noerhayati; Bambang Suprapto (Jurnal Rekayasa Sipil, 2020)
Water is one of the basic needs of living things on earth, for humans, water is very necessary for daily life. the construction of clean water facilities is very importantfor people's lives with the aim to meet the daily needs of clean water. Many waysof distributing clean water in the community one way is to use pipeline.This study aims to determine the community's clean water needs by usingpipelines in the Klagen and Ngadiboyo villages, Rejoso District, NganjukRegency. The benefits of this research are for the government's considerationthrough `related agencies for the planning of clean water distribution pipelines.The method used in this planning is the collection of technical data such as mapdata, population data, and water availability data. The research location is inNganjuk Regency, East Java, precisely in the Klagen and Ngadiboyo villages. Theresults of this study are the maximum water needs of the population until 2028,which is 63,036 m3/hour, has fulfilled the people's water needs and the simulationusing epanet has been going well with easy access using a piped waterdistribution network. Keyword: water, clean water, pipe line